The role of ultraviolet reflectance and pattern in the pollination system of Hypoxis camerooniana (Hypoxidaceae). Issue 5 (23rd September 2019) - Klomberg, Yannick; Dywou Kouede, Raissa; Bartoš, Michael; Mertens, Jan E J; Tropek, Robert; Fokam, Eric B; Janeček, Štěpán
Abstract: Apart from floral morphology and colours perceived by the human eye, ultraviolet (UV) reflectance acts as an important visual advertisement of numerous flowering plant species for pollinators. However, the effect of UV signalling on attracting pollinators of particular plant species is still insufficiently studied, especially in the Afrotropics. Therefore, we studied the pollination system of Hypoxis camerooniana in montane grasslands of Mount Cameroon, West/Central Africa. We focused mainly on the effects of the flowers' UV reflectance on its visitors. We experimentally removed UV reflection from petals either completely or partially. Thereafter, flower visitors were recorded and pistils were collected post-flowering to quantify germinated pollen tubes per treatments. The most important visitors were bees, followed by flies. Due to their contacts with reproductive organs bees are considered as the primary pollinators. Visitation rates were lower when UV reflectance was completely removed, whereas the decrease of frequency on half-treated flowers did not differ significantly from control treatments. The complete removal of UV also affected bees' landing behaviour, but not that of flies. We showed that the presence of UV reflectance is more important than UV pattern for bees visiting flowers of H. camerooniana . We hypothesize that exploiting all flowers irrespective of their pattern can be more efficient for pollinators in the open grasslands of high altitudes to spot these relatively scarce flowers by their UV reflectance. Furthermore, we highlight the necessity of both experimental and natural controls in similar studies to control for additional effects of the used UV manipulations. Abstract : Many plants advertise their flowers with UV reflectance visible to their insect visitors. By manipulating the UV reflectance and pattern of Hypoxis camerooniana in the Afromontane grasslands of Mount Cameroon, we have shown how crucial it is for the predominant visitor, bees. Both bees' preferences for flowers and their behaviour during visits are influenced by changes in UV reflectance. However, the presence of some UV signal is more important than the specific pattern. Especially in montane grasslands with higher UV irradiation, the UV floral colours are important for recognition of flowers by potential pollinators.